A water disinfection and antibacterial material and its preparation method and application

Through the preparation of bimetallic MOFs@ natural polymer composite materials, the post-synthesis exchange technology of metal salt I and natural polymer combined with metal salt II was used to solve the problems of secondary pollution, strong irritation and poor disinfection effects of existing water disinfection methods, and the effect of rapid killing and continuous inhibition of bacteria in water was achieved.

CN115886026BActive Publication Date: 2025-04-11GUANGXI UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202211206394.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-04-11
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The existing water disinfection methods have problems such as secondary pollution, strong irritation, carcinogenic risk of by-products and poor disinfection effect, especially in the disinfection of swimming pool water, it is difficult to effectively inhibit bacterial reproduction.

Method used

Using bimetallic MOFs@natural polymer composite materials, materials with rapid bactericidal and continuous antibacterial properties are prepared through in-situ synthesis method and metal ion post-synthesis exchange technology. This material is combined with metal salt I and natural polymers for post-synthesis and exchange, forming bimetal MOFs, improving antibacterial properties.

Benefits of technology

It achieves rapid killing and continuous inhibition of bacteria in water bodies (such as swimming pool water), and the material is safe and irritating, and is suitable for disinfection and sterilization of water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115886026B_ABST
    Figure CN115886026B_ABST
Patent Text Reader

Abstract

The present invention discloses a water disinfection and antibacterial material and its preparation method and application. The present invention uses natural polymer materials, metal salts and organic ligands as raw materials to prepare MOFs@natural polymer composite materials, and obtains bimetallic MOFs@natural polymer composite materials that can be used for water disinfection and antibacterial through a new strategy of post-synthesis exchange and doping metal ions. The present invention introduces a second metal ion into the MOFs component and the polymer substrate in the composite material through a post-synthesis exchange strategy to improve the antibacterial properties of the composite material; the prepared water disinfection and antibacterial material has rapid sterilization and excellent continuous antibacterial properties, can effectively kill bacteria in water (such as swimming pool water) and continuously inhibit bacterial reproduction, and is safe and non-irritating; it can be used for disinfection and sterilization of water bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a water body disinfection and antibacterial material, a preparation method thereof, and application in water body disinfection and sterilization treatment. Background Art

[0002] Water disinfection mainly uses chemical or physical methods to kill pathogens in water to prevent disease transmission and maintain the health of the population. Among them, physical disinfection methods include heating, gamma radiation and ultraviolet irradiation; chemical disinfection methods include disinfection methods such as adding heavy metal ions (such as silver and copper), alkali or acid, surfactant chemicals, oxidants (chlorine and its compounds, bromine, iodine, ozone), etc. Among these methods, oxidant disinfection is the most widely used, among which chlorine and its compounds are particularly common, followed by ozone disinfection. Ultraviolet irradiation and the method of adding bromine, iodine and their compounds are used to disinfect water used in small-scale water plants or special facilities (such as swimming pools). However, existing water disinfection materials will cause secondary pollution to the water body, and the disinfection effect of single ultraviolet or ozone disinfection is not good. Swimming pools are common places where bacteria are prone to breeding and spread. Many diseases can be transmitted through the water environment, such as typhoid, hepatitis, tuberculosis, etc. Currently, the most common method of sterilizing swimming pools is still to use chlorine-containing disinfectants. These chemicals generally have disadvantages such as pungent odor, irritation to the skin and mucous membranes, carcinogenic byproducts, and poor sustained antibacterial effect. Other alternative methods such as ozone and ultraviolet radiation also have disadvantages such as the production of toxic byproducts and short duration of effect.

[0003] Metal-organic frameworks (MOFs), also known as metal-organic coordination polymers, are a new type of porous material that has attracted widespread attention and attention from scholars in recent years. Metal-organic framework (MOFs) materials have been widely used in hydrogen storage, catalysis, drug sustained release, etc. due to their unique advantages such as high porosity, large specific surface area and easy functionalization. At the same time, MOFs are also regarded as excellent metal ion carriers and can be used as antibacterial materials. However, brittle MOFs powder is difficult to process directly, so combining MOFs with polymer materials to prepare composite materials has become an effective means to solve the MOFs processing problem. Among them, MOFs composite materials based on natural polymers have received more attention due to their wide sources and significant environmental protection and biosafety advantages. At present, the common methods for preparing MOFs@natural polymer composite materials include blending, in-situ growth, electrospinning and surface coating. Among them, the in-situ growth method based on chemical cross-linking has the advantages of high porosity of the obtained material, close combination of MOFs crystals and polymer matrix, and not easy to "fall powder", and is widely used. Generally, in the fields of antibacterial, adsorption and catalysis, the application effect of MOFs materials with a single metal component is often weaker than that of MOFs containing two or more metal components. Therefore, bimetallic metal-organic framework composites have the potential to replace traditional chlorine disinfectants for disinfection and sterilization of water bodies (such as swimming pool water), but there are currently no related research reports. Summary of the invention

[0004] The purpose of the present invention is to provide a water disinfection antibacterial material and its preparation method and application, specifically a bimetallic MOFs@natural polymer composite material with rapid bactericidal and sustained antibacterial performance and its preparation method and application in water disinfection and sterilization. The water disinfection antibacterial material has excellent antibacterial properties, can effectively kill bacteria in water (such as swimming pool water) and continuously inhibit bacterial reproduction, and is safe and non-irritating.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A water disinfection and antibacterial material is prepared using metal salt I, natural polymer, organic ligand and metal salt II as raw materials. Firstly, an MOFs@natural polymer composite material is prepared using metal salt I, natural polymer and organic ligand as raw materials through an in situ synthesis method; on this basis, a metal ion post-synthesis exchange method is adopted to use metal salt II to convert the monometallic MOFs in the composite material into bimetallic MOFs, and at the same time, a second metal ion is introduced into the natural polymer chain in the composite material.

[0007] The technical route is: natural polymer → metal ion cross-linked natural polymer matrix → MOFs@natural polymer composite materials → bimetallic MOFs@natural polymer composite materials.

[0008] The specific preparation method of the water disinfection and antibacterial material comprises the following steps:

[0009] (1) According to the weight ratio of metal salt I: natural polymer: organic ligand: metal salt II = 1-10: 2.5-20: 0.4-5: 0.1-2, the above raw materials are taken for use; the natural polymer is dissolved in water or a dilute acetic acid solution with an acetic acid mass concentration of 0.5%-5% to obtain a natural polymer solution with a mass concentration of 1%-7%; the metal salt I is dissolved in an appropriate amount of water to obtain a metal salt I solution, and then the natural polymer solution is added dropwise to the metal salt I solution, and mixed and reacted for 3-60 minutes to obtain a spherical metal ion cross-linked polymer matrix; or the metal salt I is dissolved in the natural polymer solution, and the mixed solution is added dropwise to a sodium hydroxide aqueous solution with a mass fraction of 1%-10% or a sodium tripolyphosphate aqueous solution with a mass fraction of 0.5%-5%, and the mixture is allowed to react for 20-35 minutes to obtain a spherical metal ion cross-linked polymer matrix;

[0010] (2) dissolving the organic ligand in ethanol or water to prepare an organic ligand solution of 10-100 mg / mL, adding the polymer matrix to the organic ligand solution, reacting at 25°C to 150°C for 8 to 48 hours, and obtaining a single metal MOFs@polymer composite material;

[0011] (3) Dissolve metal salt II in an appropriate amount of water, a water / ethanol mixed solvent (ethanol volume fraction is 10% to 90%), methanol or N,N-dimethylformamide to prepare a metal salt II solution, add the obtained composite material to the metal salt II solution, react at 45°C to 120°C for 24 to 48 hours, wash the product three times with deionized water, ethanol or methanol, and finally dry to obtain a bimetallic MOFs@natural polymer composite material that can be used for water disinfection and sterilization.

[0012] In the above-mentioned water disinfection and antibacterial material, the metal salt I is one of copper nitrate, copper chloride, copper sulfate, zinc chloride, zinc acetate dihydrate, zinc nitrate, zinc sulfate, chromium nitrate nonahydrate, and chromium chloride hexahydrate.

[0013] The natural polymer includes one or more of carboxymethyl chitosan, chitin, chitosan, sodium alginate, carboxymethyl cellulose and sodium lignin sulfonate.

[0014] The organic ligand is a carboxylic acid or imidazole organic ligand, and specifically one of terephthalic acid, trimesic acid, pyromellitic acid, isophthalic acid, 2-methylimidazole and 2-aminoterephthalic acid can be selected.

[0015] The metal salt II is one of silver nitrate, manganese sulfate, manganese acetylacetonate and ferric chloride hexahydrate.

[0016] Another object of the present invention is to provide an application of the water disinfection and antibacterial material in water disinfection and sterilization. Furthermore, the water disinfection and antibacterial material is used for the disinfection and sterilization of swimming pool water.

[0017] The reaction principle of the present invention is: under certain conditions, the metal ions in some types of MOFs crystals can be exchanged by another metal ion in the solvent, and in this process, the crystal structure of the MOFs material does not change. For MOFs@natural polymer composite materials, this type of reaction still holds true. Therefore, under certain conditions, metal ions II can be used to replace a part of the metal ions I in the MOFs crystals in the composite material, thereby changing the monometallic MOFs component in the composite material into bimetallic MOFs. At the same time, during the reaction process, metal ions II can also bind to the active sites (such as carboxyl, hydroxyl and amino groups) on the polymer matrix in the composite material, thereby introducing a second metal ion into the polymer matrix. The combined use of two bactericidal ions can achieve a better bactericidal effect than a single type of metal ion. The difference in the release rate of metal ions from MOFs crystals and natural polymers is used to achieve a combination of rapid bactericidal and sustained antibacterial.

[0018] The present invention uses natural polymer materials, metal salts and organic ligands as raw materials to prepare MOFs@natural polymer composite materials, and obtains bimetallic MOFs@natural polymer composite materials that can be used for antibacterial disinfection of water bodies through a new strategy of post-synthesis exchange doping of metal ions. The present invention avoids the problem that the traditional in-situ growth method is difficult to grow bimetallic MOFs on a substrate, retains the advantages of controllable preparation and stable and firm compounding of the in-situ growth method based on chemical cross-linking, and the preparation method is simple.

[0019] The beneficial effects of the present invention are:

[0020] (1) The present invention provides a new water disinfection and antibacterial material that can be used for disinfection and sterilization of water bodies, as well as a preparation method and application thereof. The preparation process of the material is simple and easy. The prepared water disinfection and antibacterial material (bimetallic MOFs@natural polymer composite material) has rapid bactericidal and excellent continuous antibacterial performance, can effectively kill bacteria in water bodies (such as swimming pool water) and continuously inhibit bacterial reproduction, and is safe and non-irritating; it can be used for continuous disinfection and sterilization of swimming pool water.

[0021] (2) The preparation method of the water disinfection antibacterial material of the present invention adopts the method of post-synthesis exchange of metal ions to convert the monometallic MOFs in the composite material into bimetallic MOFs, and at the same time introduces a second metal ion into the natural polymer chain in the composite material, thereby improving the antibacterial properties of the composite material and enhancing the application potential of the composite material.

[0022] (3) The bimetallic MOFs@natural polymer composite material prepared by the present invention has better antibacterial properties than the monometallic MOFs@natural polymer composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Infrared spectra of the Ag / Cu-BTC@CMCS composite material prepared in Example 1 and the reference materials Cu-BTC@CMCS, Cu-BTC, and Ag / Cu-BTC;

[0024] Figure 2 Energy dispersive X-ray spectroscopy (EDX) characterization spectrum of the Ag / Cu-BTC@CMCS composite material prepared in Example 1;

[0025] Figure 3 X-ray diffraction (XRD) patterns of the Ag / Cu-BTC@CMCS composite material prepared in Example 1 and the control materials Cu-BTC@CMCS, Cu-BTC, and Ag / Cu-BTC;

[0026] Figure 4 Cell survival rate results of the Ag / Cu-BTC@CMCS composite material prepared in Example 1 and its control material at different antibacterial concentrations;

[0027] Figure 5 The disinfection and sterilization effect of the Ag / Cu-BTC@CMCS composite material prepared in Example 1 on bacteria in simulated swimming pool water. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further specifically described below through embodiments.

[0029] Example 1

[0030] A water body disinfection and antibacterial material is prepared using copper nitrate, carboxymethyl chitosan, trimesic acid and silver nitrate as raw materials, and the specific preparation method thereof comprises the following steps:

[0031] (1) According to the weight ratio of copper nitrate: carboxymethyl chitosan: trimesic acid: silver nitrate = 5:2.5:1.5:0.3, the above raw materials are taken for use; carboxymethyl chitosan is dissolved in water to prepare a carboxymethyl chitosan solution with a mass concentration of 4%, copper nitrate is dissolved in an appropriate amount of water to prepare a 50 mg / mL copper nitrate solution, the carboxymethyl chitosan solution is added dropwise to the copper nitrate solution, and mixed for reaction for 5 minutes to obtain a spherical copper ion cross-linked polymer matrix;

[0032] (2) Dissolve trimesic acid in ethanol to prepare a 20 mg / mL trimesic acid ethanol solution, add the above polymer matrix into a polytetrafluoroethylene-lined hydrothermal reactor containing the trimesic acid ethanol solution, and react at 80°C for 24 hours to obtain a spherical single metal Cu-BTC@CMCS composite material;

[0033] (3) Silver nitrate was dissolved in a water / ethanol mixed solvent (ethanol volume fraction was 50%) to prepare a 2 mg / mL silver nitrate solution. The obtained composite material was added to the silver nitrate solution and hydrothermally reacted at 95 °C for 24 h. The product was washed three times with deionized water and finally freeze-dried to obtain the silver-copper bimetallic Ag / Cu-BTC@CMCS composite material.

[0034] Example 2

[0035] A water disinfection and antibacterial material is prepared using zinc nitrate, chitosan, 2-methylimidazole and manganese acetylacetonate as raw materials, and the specific preparation method thereof comprises the following steps:

[0036] (1) According to the weight ratio of zinc nitrate: chitosan: 2-methylimidazole: manganese acetylacetonate = 1:3:4:1, the above raw materials are taken for use; chitosan is dissolved in dilute acetic acid with a mass concentration of 1% to obtain a chitosan solution with a mass concentration of 3%, zinc nitrate is added to the chitosan solution under mechanical stirring, and mixed and reacted for 60 minutes to obtain a cross-linking solution, and the cross-linking solution is dripped into a sodium hydroxide aqueous solution with a mass concentration of 4% through a syringe and allowed to stand for 20 minutes to obtain a spherical zinc ion cross-linked polymer matrix;

[0037] (2) Dissolving 2-methylimidazole in water to prepare a 50 mg / mL 2-methylimidazole solution, adding the polymer matrix to the 2-methylimidazole solution, and reacting at 25°C for 24 hours to obtain a single metal MOFs@polymer composite material;

[0038] (3) Manganese acetylacetonate was dissolved in methanol to prepare a 30 mg / mL manganese acetylacetonate methanol solution. The obtained composite material was added to the manganese acetylacetonate methanol solution and reacted at 60 °C for 24 h. The product was washed three times with methanol and deionized water, respectively, and finally freeze-dried to obtain a zinc-manganese bimetallic MOFs@natural polymer composite material that can be used for water disinfection and sterilization.

[0039] Example 3

[0040] A water disinfection and antibacterial material is prepared using chromium nitrate nonahydrate, chitosan, terephthalic acid and ferric chloride hexahydrate as raw materials, and the specific preparation method thereof comprises the following steps:

[0041] (1) According to the weight ratio of chromium nitrate nonahydrate: chitosan: terephthalic acid: ferric chloride hexahydrate = 1:4:0.6:0.5, the above raw materials are taken for use; chitosan is dissolved in dilute acetic acid with a mass concentration of 1% to obtain a chitosan solution with a mass concentration of 2%, and then chromium nitrate nonahydrate is added to the chitosan solution and stirred to dissolve to obtain a cross-linking solution; the cross-linking solution is dripped into a sodium tripolyphosphate aqueous solution with a mass concentration of 2% through a syringe, and the cross-linking solution is allowed to stand for 30 minutes to obtain a spherical chromium ion cross-linked polymer matrix;

[0042] (2) dissolving terephthalic acid in an appropriate amount of water to prepare a 30 mg / mL terephthalic acid aqueous solution, adding the polymer matrix to the terephthalic acid aqueous solution, hydrothermally reacting at 150°C for 8 h, washing with deionized water and freeze-drying to obtain a single metal MOFs@polymer composite material;

[0043] (3) Ferric chloride hexahydrate was dissolved in an appropriate amount of N,N-dimethylformamide (DMF) to prepare a 1 mg / mL ferric chloride DMF solution. The obtained composite material was added to the ferric chloride DMF solution and refluxed at 110°C for 24 h. The product was washed three times with ethanol and deionized water, respectively, and finally dried at 85°C to obtain a chromium-iron bimetallic MOFs@natural polymer composite material that can be used for water disinfection and sterilization.

[0044] Example 4

[0045] A water disinfection and antibacterial material is prepared using chromium nitrate nonahydrate, sodium alginate, terephthalic acid and ferric chloride hexahydrate as raw materials, and the specific preparation method thereof comprises the following steps:

[0046] (1) According to the weight ratio of chromium nitrate nonahydrate: sodium alginate: terephthalic acid: ferric chloride hexahydrate = 1:4:0.6:0.5, the above raw materials are taken for use; sodium alginate is dissolved in an appropriate amount of water to prepare a sodium alginate solution with a mass concentration of 2%, and then chromium nitrate nonahydrate is added to the sodium alginate solution and stirred to dissolve to obtain a cross-linking solution; the cross-linking solution is dripped into a sodium tripolyphosphate aqueous solution with a mass concentration of 2% through a syringe, and the cross-linking solution is allowed to stand for 30 minutes to obtain a spherical chromium ion cross-linked polymer matrix;

[0047] (2) dissolving terephthalic acid in an appropriate amount of water to prepare a 30 mg / mL terephthalic acid aqueous solution, adding the polymer matrix to the terephthalic acid aqueous solution, hydrothermally reacting at 150°C for 8 h, washing with deionized water and freeze-drying to obtain a single metal MOFs@polymer composite material;

[0048] (3) Ferric chloride hexahydrate was dissolved in an appropriate amount of N,N-dimethylformamide (DMF) to prepare a 1 mg / mL ferric chloride DMF solution. The obtained composite material was added to the ferric chloride DMF solution and refluxed at 110°C for 24 h. The product was washed three times with ethanol and deionized water, respectively, and finally dried at 85°C to obtain a chromium-iron bimetallic MOFs@natural polymer composite material that can be used for water disinfection and sterilization.

[0049] Comparative Example 1

[0050] Step (1) and step (2) are the same as those in Example 1, except that step (3) is omitted, and the product obtained in step (2) is dried at 60° C. for 24 h to obtain a Cu-BTC@CMCS composite material.

[0051] Product Characterization and Performance Testing of Example 1

[0052] Taking the Ag / Cu-BTC@CMCS composite material prepared in Example 1 as an example, and taking pure Cu-BTC and Cu-BTC@CMCS as controls, the following characterization and performance tests were performed:

[0053] (1) Fourier transform infrared spectrometer (FT-IR) characterization

[0054] pass Figure 1 FT-IR tests show that the characteristic peaks of Cu-BTC appear on both Cu-BTC@CMCS and Ag / Cu-BTC@CMCS composites, indicating that MOFs grow on natural polymer substrates; at the same time, the new peaks appearing on the Ag / Cu-BTC@CMCS composite prove the successful doping of silver ions in Cu-BTC crystals, indicating the successful preparation of the bimetallic composite.

[0055] (2) Energy dispersive X-ray spectroscopy (EDX) characterization

[0056] pass Figure 2 The EDX test shows that copper and silver elements are widely distributed on the Ag / Cu-BTC@CMCS composite material, further indicating the successful preparation of the bimetallic composite material.

[0057] (3) X-ray diffraction (XRD) characterization

[0058] The sample was scanned by X-ray diffractometer at 2θ=5-50°. The test results are as follows: Figure 3 As shown, the characteristic peaks of Cu-BTC appear on both Cu-BTC@CMCS and Ag / Cu-BTC@CMCS composites, indicating that the silver ion exchange process does not affect the structure of MOFs crystals.

[0059] (4) Antibacterial performance test

[0060] The antibacterial effect of the material on Escherichia coli and Staphylococcus aureus was evaluated by the size of the inhibition zone. 7 CFU / mL) was evenly coated on the surface of the culture medium, the culture medium was perforated, and then the same mass of Ag / Cu-BTC@CMCS composite material and Cu-BTC@CMCS composite material were weighed and placed in the holes respectively, and cultured at 37°C for 24-36h, and the size of the inhibition zone was observed. The experimental results are shown in Table 1. It can be seen from Table 1 that the size of the inhibition zone of the Ag / Cu-BTC@CMCS composite material against Escherichia coli and Staphylococcus aureus is significantly increased compared with the Cu-BTC@CMCS composite material, indicating that the antibacterial performance of the Ag / Cu-BTC@CMCS composite material containing silver and copper bimetallic is better than that of the Cu-BTC@CMCS composite material containing only a single metal.

[0061]

[0062] (5) Cytotoxicity assessment

[0063] Using HeLa cells as a model, the cells were mixed with the composite materials and cultured, and then the cell survival rate was measured. Figure 4 As shown, the cell survival rate of the Ag / Cu-BTC@CMCS composite material at its antibacterial concentration reached 87.3%, indicating that the Ag / Cu-BTC@CMCS composite material has limited toxicity to cells and has high biosafety.

[0064] (6) Swimming pool water disinfection application test

[0065] Use simulated swimming pool water to test the disinfection application effect of the product material of the present invention. Figure 5 As shown, the Ag / Cu-BTC@CMCS composite material can quickly kill bacteria in swimming pool water and inhibit bacterial reproduction for a long time, indicating that the Ag / Cu-BTC@CMCS composite material can be used for disinfection and sterilization of swimming pool water.

Claims

1. A water disinfection and antibacterial material, characterized in that: It is prepared using metal salt I, natural polymer, organic ligand and metal salt II as raw materials, and its specific preparation method includes the following steps: (1) According to the weight ratio of metal salt I: natural polymer: organic ligand: metal salt II = 1-10: 2.5-20: 0.4-5: 0.1-2, the above raw materials are taken for use; the natural polymer is dissolved in water or a dilute acetic acid solution with an acetic acid mass concentration of 0.5%-5% to obtain a natural polymer solution with a mass concentration of 1%-7%; the metal salt I is dissolved in an appropriate amount of water to obtain a metal salt I solution, and then the natural polymer solution is added dropwise to the metal salt I solution, and mixed and reacted for 3-60 minutes to obtain a spherical metal ion cross-linked polymer matrix; or the metal salt I is dissolved in the natural polymer solution, and the mixed solution is added dropwise to a sodium hydroxide aqueous solution with a mass fraction of 1%-10% or a sodium tripolyphosphate aqueous solution with a mass fraction of 0.5%-5%, and the reaction is allowed to stand for 20-35 minutes to obtain a spherical metal ion cross-linked polymer matrix; (2) dissolving the organic ligand in ethanol or water to prepare an organic ligand solution of 10-100 mg / mL, adding the polymer matrix to the organic ligand solution, reacting at 25°C to 150°C for 8 to 48 hours, and obtaining a single metal MOFs@polymer composite material; (3) dissolving metal salt II in an appropriate amount of water, a water / ethanol mixed solvent with an ethanol volume fraction of 10% to 90%, methanol or N,N-dimethylformamide to prepare a metal salt II solution, adding the obtained composite material to the metal salt II solution, reacting at 45°C to 120°C for 24 to 48 hours, washing the product with deionized water, ethanol or methanol for three times, and finally drying to obtain a bimetallic MOFs@natural polymer composite material that can be used for water disinfection and sterilization; The metal salt I is one of copper nitrate, copper chloride, copper sulfate, zinc chloride, zinc acetate dihydrate, zinc nitrate, zinc sulfate, chromium nitrate nonahydrate, and chromium chloride hexahydrate; The natural polymer includes one or more of chitin, chitosan, sodium alginate and carboxymethyl cellulose; The organic ligand is one of terephthalic acid, trimesic acid, pyromellitic acid, isophthalic acid, 2-methylimidazole, and 2-aminoterephthalic acid; The metal salt II is one of silver nitrate, manganese sulfate, manganese acetylacetonate and ferric chloride hexahydrate.

2. The water disinfection and antibacterial material according to claim 1, characterized in that: The natural macromolecule is carboxymethyl chitosan.

3. Use of the water disinfection and antibacterial material as claimed in claim 1 or 2 in water disinfection and sterilization treatment.

4. The use according to claim 3, characterized in that The water disinfection and antibacterial material is used for disinfection and sterilization of swimming pool water.

Citation Information

Patent Citations

  • Method for macroscopically preparing MOFs (metal-organic framework)@natural polymer novel composite material

    CN109320733A

  • Preparation method of chitosan-metal organic framework antibacterial material

    CN110903488A

  • Bimetal nanostructure antibacterial composition and preparation method thereof

    CN114223671A

  • Dual metal mofs catalyst, and preparation method therefor and use thereof

    WO2021088196A1

  • Preparation method for mofs photocatalytic material having high visible light response

    WO2021258233A1